Initial public offering (IPO) underpricing in China A -share market - zhao, qijun (2015)
Research in literature illustrates that initial public offerings (IPO) price are underestimated in the primary market. This paper investigates 270 new issue shares from 10th January 2011 to 30th December 2014 excluding data from 2013 because CSRC postponed IPO; I find that the average market-adjusted return is 60.72%. The cross-sectional analysis is used to measure the proxy variables of hypothesis. I find strong evidence for speculation effect hypothesis and inequality supply and demand of new share hypothesis and weak evidence for information asymmetry hypothesis, moreover, split share structure hypothesis is failed to explain IPO underpricing in China A-share stock market. Generally, IPO underpricing is caused by current issue system and irrational investment behavior.